Diagnosis of the Difficulties of the Oral Expression of the B1 Level Students of the French Alliance of San Luis Potosí / Mexico - Mounkoro, Ismaila (2021)
The purpose of this article was to diagnose the difficulties in oral competence presented by students of French as a foreign language aspiring to level B1 of Alliance Française in San Luis Potosí (Mexico). A quantitative and qualitative study was carried out, two instruments were used to collect the data: a socioformative analitic rubric to evaluate oral competence through five components (pronunciation, vocabulary, coherence and cohesion, grammatical competence and interaction) and semi-structured interviews were conducted with 17 evaluators. A sample of 247 Spanish-speaking students aged between 13 and 45 participated in the evaluation. The results showed that the main difficulty is the lack of vocabulary and the factors found are the influence of the mother tongue and a second language that is English, as well as fear of native teachers. In-depth studies are suggested on each of the difficulties encountered.